CORRELATION AND REGRESSION ANALYSIS OF PATTERNS OF CHANGES IN WATER CONSUMPTION IN ECONOMIC SECTORS - Seytov, Aybek; Kutlimuradov, Yusup (Techscience uz - Topical Issues of Technical Sciences, 2025)
This paper analyzes the state of water resource use in regional conditions and their distribution across key economic sectors. The degree of interdependence and the impact of water consumption in various economic sectors were assessed using correlation and regression models. The results obtained make it possible to improve the efficiency of water resource management, ensure optimal allocation, and identify promising development areas. The study's findings can be used to analyze the current state of water consumption by sector and to assess the potential for optimal water resource allocation in the future.